ChemInform Abstract: Palladium‐Catalyzed Allylic Alkylation Reactions of Glycolates as a Tool for the Synthesis of Functionalized α‐Hydroxy Esters. Issue 4 (January 2016) - Kiefer, Alexander; Gawas, Dnyaneshwar; Kazmaier, Uli
Abstract: An optimized protocol allows the introduction of side chains into the tert‐butyl glycolate (I) using allyl acetates.